An Index to assess areas hydrothermally suitable for rubber cultivation - Rao P S; Jayarathnam K; Sethuraj M R (Indian Journal of Natural Rubber Rsearach, 1993)
A simple climatic index (CI) was developed, incorporating temperature and rainfall distribution, with respect to the climatic requirements of hevea brasiliensis. The climatic resources for rainfed rubber cultivation have been categorised into siz zones: 1. Highly suitable, (2) suitable, (3) moderate, (4) marginal, (5) conditional and (6) not favourable. Comparison of CI with already established commercial natural rubber growing regions elsewhere indicates that most of hte locations in India, where commercial cultivation of rubber is being undertaken, fall under zones 2 and 3. Temperature conditions along Westa caost, parts of east coast and a few locations in North-East India are more favourable for rubber cultivation than rainfall. Areas marginally or conditionally suitable for rubber cultivation in different parts of India, with irrigation and soil conservation, are reported.
Keywords: Climatic requirement; Climatic suitability; Drought; Hevea brasiliensis; India; Marginal area; Rainfed cultivation